Standardization of the formulation and freezing of native potato Solanum phureja llapingachos - Bustamante Melo, Jesus; Jarrin, Verónica Fernanda; Paredes Rosero, Diego Andrés; Benavides Patiño, Jesús Emilio (Revista Colombiana de Investigaciones Agroindustriales, 2021)
The habit of food consumption by people has been modified; this change is related to a greater concern for health and easy food preparation. For this reason, the elaboration of potato tortillas type llapingacho was standardized in the quantification of ingredients, the cooking method, quick freezing, and reconstitution. A variety of native potato (Solanum phureja) was used, the organoleptic characteristics of the product were evaluated and the analysis of the variables was carried out with inferential statistics (p < 0.05). The results showed that the best formulation was with 8 g of salt, 3 g of garlic, and 4 g of onion per kg of mashed potatoes, the cooking and reconstitution method corresponded to roasting on a low flame griddle with a time of 5 min for each side. Similarly, for freezing it was observed that the internal temperature of the blast chiller was -40 °C. It is concluded that the native potato tortilla type llapingacho is an appetizing product for the consumer and that it shows adequate characteristics for its industrialization.